„Nicea albo śmierć”, czyli polski dyskurs polityczny na temat Traktatu ustanawiającego Konstytucję dla Europy i jego wpływ na stosunki polsko-niemieckie - Bielawska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
This paper analyzes the discussions and statements of Polish politicians concerning the system of decision-making in the Council of the European Union in the period after the European Convention concluded its work and the Treaty on a Constitution for Europe was signed. Particular attention is paid to the influence this discourse and the attitudes of political leaders exerted on Polish-German relations.